Study on the Noise Characteristic of Synchronous Belt Drive based on Wavelet Decomposition - Yaochen Shi; Xuechen Zhang; Guoping Chen; Xuelian Yu (Jixie chuandong)
The drive noise of synchronous belt can be divided into meshing impact noise， transverse vibration noise， air flow noise and friction noise. In order to study the frequency distribution characteristics of automobile synchronous belt noise signal， firstly， the frequency domain distribution of various noises of synchronous belt drive is analyzed theoretically. Then， the variable speed and variable tension test is carried out for ZA type automobile synchronous belt. Finally， based on the analysis method of wavelet decomposition， the frequency distribution characteristics of the drive noise signal are obtained. The results show that with the increase of rotating speed， the meshing impact noise increases， and the proportion of meshing impact noise energy in the noise source of synchronous belt drive increases. The meshing impact noise is mainly concentrated in the low frequency band， and the transverse vibration noise is mainly concentrated in the high frequency band. It provides basis for vibration and noise reduction of automobile engine.